Review of Rubber-Based Waste in Compressed Bricks - Tan A.S.; Tan J.C.; Ean L.W.; Ng C.Y.; Mohammed B.S.; Norhisham S. (Springer Science and Business Media Deutschland GmbH, 2025)
The management of the production and post-use waste disposal from rubber-based materials production or rubber waste has been a concern as it might negatively impact the environment, e.g. water and soil pollution. Henceforth, this study investigates the feasibility of utilizing rubber waste in compressed rubberized bricks. This study discusses the source of rubber waste and the design parameters for the mix ratio of compressed bricks and rubber waste. Compressive strength and water absorption were observed to examine the behaviour of the compressed bricks. ? 2024, Institute of Technology PETRONAS Sdn Bhd.